Acute hypoxic preconditioning prevents palmitic acid‐induced cardiomyocyte apoptosis via switching metabolic GLUT4‐glucose pathway back to CD36‐fatty acid dependent. Issue 4 (15th January 2018) - Chen, Yeh‐Peng; Kuo, Wei‐Wen; Baskaran, Rathinasamy; Day, Cecilia‐Hsuan; Chen, Ray‐Jade; Wen, Su‐Ying; Ho, Tsung‐Jung; Padma, Viswanadha Vijaya; Kuo, Chia‐Hua; Huang, Chih‐Yang
Abstract: Metabolic syndrome is a risk factor for the development of cardiovascular diseases. Myocardial cell damage leads to an imbalance of energy metabolism, and many studies have indicated that short‐term hypoxia during myocardial cell injury has a protective effect. In our previous animal studies, we found that short‐term hypoxia in the heart has a protective effect, but long‐term hypoxia increases myocardial cell injury. Palmitic acid (PA)‐treated H9c2 cardiomyoblasts and neonatal rat ventricle cardiomyocytes were used to simulate hyperlipidemia model, which suppress cluster of differentiation 36 (CD36) and activate glucose transporter type 4 (GLUT4). We exposed the cells to short‐ and long‐term hypoxia and investigated the protective effects of hypoxic preconditioning on PA‐induced lipotoxicity in H9c2 cardiomyoblasts and neonatal rat cardiomyocytes. Preconditioning with short‐term hypoxia enhanced both CD36 and GLUT4 metabolism pathway protein levels. Expression levels of phospho‐PI3K, phospho‐Akt, phospho‐AMPK, SIRT1, PGC1α, PPARα, CD36, and CPT1β induced by PA was reversed by short‐term hypoxia in a time‐dependent manner. PA‐induced increased GLUT4 membrane protein level was reduced in the cells exposed to short‐term hypoxia and si‐PKCζ. Short‐term hypoxia, resveratrol and si‐PKCζ rescue H9c2 cells from apoptosis induced by PA and switch the metabolic pathway from GLUT4 dependent to CD36 dependent. We demonstrate short‐term hypoxic preconditioning as a more efficient way as resveratrol in maintaining the energy metabolism of hearts during hyperlipidemia and can be used as a therapeutic strategy. Abstract : In general situation, the heart use energy source from fatty acid and glucose. We used short‐term hypoxia, resveratrol and si‐PKCζ treatment to demonstrate that SIRT1 and PKCζ could regulated the switch the pathways as foremost point under the PA treatment, in our results, short‐term hypoxia could reverse the H9c2 use the fatty acid as energy source and a little glucose, but long‐term hypoxia both reduced the muscle contraction pathway and insulin signaling pathway.